Risk Management in Financial Technology: A Systematic Literature Reviewto Support Sustainability and Security of Digital Financial Services - Mega Fitri Yani; Cindy Muhdiantini; Syifa Nur Aini (SITEKNIK: Sistem Informasi, Teknik dan Teknologi Terapan, 2025)
The rapid growth of the financial technology (FinTech) sector has revolutionized financial services by enhancing convenience, speed, and efficiency. However, this expansion also introduces significant risks, necessitating robust information technology (IT) risk management strategies. This study systematically reviews the existing literature on FinTech risk management, focusing on frameworks, algorithms, policies, and technical aspects that influence risk management practices. By integrating advanced algorithms such as Artificial Intelligence and Deep Forest with established frameworks like ISO 31000:2018 and NIST, the research provides a comprehensive perspective on managing risks in FinTech, bridging gaps not extensively covered in previous studies. A systematic literature review methodology identified and analyzed 17 key studies from an initial pool of 134 documents sourced from databases such as Scopus and Google Scholar. Findings highlight the critical role of advanced technologies and established frameworks in mitigating risks and underscore the need for continuous adaptation to evolving challenges. This research offers valuable insights for financial institutions and policymakers, promoting sustainable and secure digital financial services.